Experimental Design in Plasma Welding of SUS 304 Stainless Steel Thin Plates - Hung Ha , Minh; Vu , Duong; Tinh Do , Hai (Universitas Ahmad Dahlan, 2023)
Background: This research focuses on the evaluation of the independent influence and the bidirectional interaction of some welding parameters in butt welding for the SUS 304 stainless steel thin plates using the automatic plasma welding system (450 +/- Plasma, SP7Turmatic from Lincoln). Contribution: The findings will serve as a reliable background to design the mathematical model for the prediction of the tensile strength for the plasma welding of steel SUS 304 thin plates in terms of the nomination of the optimal process for adopting the requirement in industry. Method: The welding setting is nominated for 04 main changing parameters, such as the peak current of welding (Ih, A); the background current of welding (Ib, A); the welding speed (vh, cm/min); the feeding rate of the welding wire (vc.d, cm/min); the diameter of the wire (d = 1.0 mm); and the flow rate of the shielding gas (Gk.p, 2.0 l/min). Mathematical statistics software ANOVA using to analyze the influence of the parameters on the tensile strength of the weld as the target function. Results: The tensile strength of the plasma welding samples is about 650 MPa at the equivalent level of the other publications. This proved the reasonable welding setting for the preliminary investigation. Conclusion: Authors proved the nomination of the main plasma welding technological parameters, such as the peak current, the background current, the welding speed, and the feeding rate of the wire, is reasonable towards the maximum tensile strength, one of the important criteria in the weld performance